2008
DOI: 10.1152/ajpgi.90206.2008
|View full text |Cite
|
Sign up to set email alerts
|

Essential fatty acid deficiency in mice impairs lactose digestion

Abstract: Essential fatty acid (EFA) deficiency in mice induces fat malabsorption. We previously reported indications that the underlying mechanism is located at the level of the intestinal mucosa. We have investigated the effects of EFA deficiency on small intestinal morphology and function. Mice were fed an EFA-deficient or control diet for 8 wk. A 72-h fat balance, the EFA status, and small intestinal histology were determined. Carbohydrate absorptive and digestive capacities were assessed by stable isotope methodolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 44 publications
1
9
0
Order By: Relevance
“…Hematoxylin and eosin (H&E) staining was done on 3-m-thick sections of formalin-and PFA-fixed jejunal segments to assess histology, according to standard procedures. Morphometric analysis was carried out as described previously (20). Villus and crypt length were measured manually in well-orientated sections (10 measurements/rat) from digitized images that were evaluated at ϫ10 magnification (1 pixel ϭ 0.397 m) using a calibrated image analysis system (Qwin V3.0; Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Hematoxylin and eosin (H&E) staining was done on 3-m-thick sections of formalin-and PFA-fixed jejunal segments to assess histology, according to standard procedures. Morphometric analysis was carried out as described previously (20). Villus and crypt length were measured manually in well-orientated sections (10 measurements/rat) from digitized images that were evaluated at ϫ10 magnification (1 pixel ϭ 0.397 m) using a calibrated image analysis system (Qwin V3.0; Leica Microsystems).…”
Section: Methodsmentioning
confidence: 99%
“…[ (35) by gas chromatography-mass spectometry (Agilent 5957C Series GC/MSD; Agilent Technologies, Amstelveen, The Netherlands) as has been done previously (20). The calculations for blood glucose kinetics were described recently by Van Dijk (34) and Laskewitz (18).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Bile salts are essential for bile production, secretory processes, and efficient intestinal absorption of dietary fat. In our laboratory we developed a mouse model to study the effects of EFA deficiency in vivo (31,49). Previous studies in this mouse model have shown that EFA deficiency-associated fat malabsorption is not caused by impaired bile formation, as has been implied earlier in a rat model for EFA deficiency (28).…”
Section: Lukovac S Los El Stellaard F Rings Eh Verkade Hjmentioning
confidence: 99%
“…4141.08) and EFA-sufficient (control, no. 4141.07) diets (16 wt% and 34 energy% fat), which were custom synthesized by Arie Bloks (Woerden, the Netherlands) (31,49). Essentially, unsaturated fatty acids in EFA-sufficient diet were replaced by saturated fatty acid in an EFA-deficient diet; the EFA-deficient diet was particularly reduced in linoleic acid (essential fatty acid) concentration.…”
Section: Experimental Dietsmentioning
confidence: 99%